Efek Penggaraman Kering Terhadap Karakteristik Sensori dan Kadar Air Ikan Kuwe Asin (Caranx sp.) - Obyn Imhart Pumpente; Novalina Maya Sari Ansar; Wendy Alexander Tanod (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Kuwe (Caranx sp.) is a captured fishery commodity in the Sangihe Islands. The abundant catch of fish makes it difficult for fishermen to market because the local market in the Sangihe Islands cannot absorb it, and there is no cold storage with a large capacity to maintain the quality of fish. One of the ways to increase the durability is if the production of kuwe fish is abundant, namely by the dry salting method. The dry salting technique is relatively straightforward, so the community can apply it. This study aimed to observe the sensory characteristics and moisture content of salted kuwe fish products using the dry salting method. The research method was cleaning and fileting the kuwe fish meat, then dry salting with a salt concentration of 10%, 15%, and 20%, and drying in the sun. The results showed that the sensory test for salted fish appearance, aroma, taste, and texture was best at 15% salt concentration, with panelist values of 8.65, 8.20, 7.95, and 8.50 (respectively). The water content of salted fish at a salt concentration of 15% is 28.20%. The sensory characteristics and water content of salted kuwe fish wih salt concentration of 15% have complied with SNI 8273:2016, namely a minimum of 7 and a maximum of 40%.